Floral phenology, secondary pollen presentation and pollination mechanism in Inula racemosa (Angiosperms: Asteraceae) - P.A. Shabir; I.A. Nawchoo; A.A. Wani (Journal of Threatened Taxa, 2013)
Inula racemosa Hook. f. is protandrous, discharges pollen grains inside the anther tube and presents pollen secondarily onto the sweeping hairs of the style. The style and stigmatic branches present the yellow clumped pollen grains for pollination. This study describes floral functional morphology and phenology, anther dehiscence and pollen presentation, growth and behaviour of style during anthesis and pollination mechanism of I. racemosa. The species is entomophilous and is characterized by a highly asynchronous sexual phase. A large degree of asynchrony from floret to floret in a capitulum, and capitulum to capitulum in a plant, keeps the pollen dispersed for a longer duration. Two insect families were represented in the pollinator survey: Hymenoptera and Diptera. A significant correlation was observed between the number of capitula visited per bout and foraging time. We discuss morphological features of the ?owers which may enhance the pollen removal rate per bee visit and consequently cause a high visitation and pollination rate.